CTX-M-27 Producing Salmonella enterica Serotypes Typhimurium and Indiana Are Prevalent among Food-Producing Animals in China - Zhang, Wen-Hui; Lin, Xiang-Yan; Xu, Liang; Gu, Xi-Xi; Yang, Ling; Li, Wan; Ren, Si-Qi; Liu, Ya-Hong; Zeng, Zhen-Ling; Jiang, Hong-Xia (Frontiers in Microbiology, 2016)
Salmonella spp. are one of the most important food-borne pathogens causing digestive tract and invasive infections in both humans and animals. Extended-spectrum β-lactamases (ESBLs) especially the CTX-M-type ESBLs are increasingly being reported worldwide and in China. These studies seldom focused on Salmonella isolates from food-producing animals. The aim of this study was to characterize the antimicrobial resistance profiles, serotypes and ESBLs and in particular, CTX-M producing Salmonella isolates from chickens and pigs in China. Salmonella isolates were identified by API20E system and polymerase chain reaction (PCR) assay; serotypes were determined using slide agglutination with hyperimmune sera; antimicrobial susceptibility was tested using the ager dilution method; the prevalence of ESBLs genes were screened by PCR; CTX-M-producing isolates were further characterized by conjugation along with genetic relatedness and plasmid replicon type. In total, 159 Salmonella strains were identified, among which 95 strains were S. enterica serovar Typhimurium, 63 strains were S. enterica serovar Indiana and 1 strain was S. enterica serovar Enteritidis. All of these isolates presented multi-drug resistant phenotypes. Forty-five isolates carried CTX-M genes, the most common subtype was CTX-M-27(34), followed by CTX-M-65(7) and CTX-M-14(4).Most blaCTX-M genes were transmitted by non-typeable or IncN/IncFIB/IncP/IncA/C/IncHI2 plasmids with sizes ranging from 80 to 280 kb. In particular, all the 14 non-typeable plasmids were carrying blaCTX-M-27 gene and had a similar size. PFGE profiles indicated that CTX-positive isolates were clonally related among the same serotype, whilst the isolates of different serotypes were genetically divergent. This suggested that both clonal spread of resistant strains and horizontal transmission of the resistance plasmids contributed to the dissemination of blaCTX-M-9G-positive Salmonella isolates. The presence and spread of CTX-M,especially the CTX-M-27 in S. enterica serovars Typhimurium and Indiana in food-producing animals poses a great threat for public health. Control strategies to limit the dissemination of these strains through the food chain are necessary.